Особливості реалізації некооперативної стратегії в міжкультурному дискурсі - Котов, Михайло Володимирович (Волинський національний університет ім. Лесі Українки, 2013)
У статті проаналізовано особливості реалізації некооперативної стратегії в ситуації спілкування представників декількох різних культур англійською мовою при мовленнєвій адаптації. Комуніканти схарактеризовано як полікультурні дискурсивні особистості, які проходять дві стадії розвитку – етноцентризму та етнорелятивізму. На шляху до досягнення мети комунікації, спілкуючись у маргінальній зоні дискурсивного оточення, співрозмовники в межах некооперативної стратегії вдаються до реалізації набору тактик – негативної стереотипізації, маніфестації відчуженості, агресії.

The article deals with the specificity of realization of non-cooperative strategy in the situation of interaction of the representatives of different cultures using the English language within the framework of adaptation processes. Communicants are regarded as polycultural discursive personalities. They pass several stages of development – ethnocentrist and ethnorelativist. Trying to achieve the goal of communication while interacting in the marginal zone of discursive surroundings, interlocutors realize a number of tactics within the framework of the non-cooperative strategy – negative stereotypization, manifestation of alienation, aggression. Each of the abovementioned tactics is characterized by the specificity of verbal representation at lexical and syntactic levels in intercultural discourse. The latter influences the construction of intersubjectivity, which determines the successfulness of the act of communication.
Specificity of Realization of Non-Cooperative Strategy in Intercultural Discourse
Keywords: міжкультурний дискурс; некооперативна стратегія; мовленнєва адаптація; полікультурна дискурсивна особистість; етноцентризм; етнорелятивізм; маргінальна зона дискурсивного оточення; intercultural discourse; non-cooperative strategy; adaptation; polycultural discursive personality; ethnocentrism; ethnorelativism; marginal zone of discursive surroundings